Remembering - but not knowing - disturbs the relational bindings newly established in short-term/working memory: an age-group comparison. - Boujut, Arnaud; Clarys, David (Aging, Neuropsychology & Cognition, 2018)
The aim of this study was to highlight that episodic memory and working memory compete for the same resource, which would be diminished in aging. Using the remember/know paradigm, we compared the interference related to the retrieval of words on the parallel processing of preestablished relational bindings (Shifting condition) or newly established relational bindings (Updating condition). Within each age-group, participants had comparable performances in remembering across recognition conditions. However, the results showed that only updating activity was impaired after a remember response was given in the younger group. This specific interaction between updating and remembering - but not knowing - tends to indicate that both working memory and episodic memory rely on the ability to establish contextualized representations. In the older group, the performance in updating activity was impaired regardless of the kind of the competing retrieval. Limitations in terms of interference hypothesis and limited resource hypothesis are discussed.